SYNTHESIS AND STUDY OF STRUCTURAL PROPERTIES OF COMPOSITES BASED ON NI-RU FOR STEAM CONVERSION OF ETHANOL - S.M. Naurzkulova; B.K. Massalimova; K.A. Shorayeva; G.М. Dzhienbaeva; Arapova M.V; V.A. Sadykov (Academic Scientific Journal of Chemistry, 2020)
Сatalyst precursors, substituted by rare-earth and transition metals, promoted with Ru nanoparticles using the modified Pechinimethod (Organic polymeric precursor) have been synthesized. To transform biofuel (ethanol) into hydrogen from the obtained active phases, three different methods were used to synthesize composites with the general formula [LaMn1-xBxO3 + δ / Ln1-yZryO2] (1: 1 by mass), B = Ni, Ru, Ln = Pr, Sm , Ce. Structural and surface properties of the obtained samples of complex oxides and composites were studied using the BET and XPA methods. The textural and structural characteristics of composites differing in the methods of their preparationare presented